Dark matter production via a non-minimal coupling to gravity. Issue 2 (1st February 2023) - Lebedev, Oleg; Solomko, Timofey; Yoon, Jong-Hyun
Abstract: We study postinflationary scalar dark matter production via its non-minimal coupling to gravity. During the inflaton oscillation epoch, dark matter is produced resonantly for a sufficiently large non-minimal coupling ξ ≳ 5. We find that backreaction on the curvature and rescattering effects typically become important for the values of ξ above 30, which invalidate simple estimates of the production efficiency. At large couplings, the dark matter yield becomes almost independent of ξ, signifying approximate quasi-equilibrium in the inflaton-dark matter system. Although the analysis gets complicated by the presence of apparent negative energy in the Jordan frame, this behaviour can be regularized by introducing mild dark matter self-interaction. Using lattice simulations, we delineate parameter space leading to the correct dark matter relic abundance.